2007
DOI: 10.1002/gps.1821
|View full text |Cite
|
Sign up to set email alerts
|

Group reminiscence therapy for cognitive and affective function of demented elderly in Taiwan

Abstract: Participation in reminiscence activities can be a positive and valuable experience for demented older persons. Consequently, the development of a structured care program for elderly persons with cognitive impairment and the need for long-term care is essential. Thus, health providers in long-term care facilities should be trained in reminiscence group therapy, and to be able to deliver such a program to the targeted group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
127
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(143 citation statements)
references
References 29 publications
(29 reference statements)
11
127
1
4
Order By: Relevance
“…This finding was consistent with the results in several previous studies (Ashida, 2000;Haight et al, 2000;Jones, 2003;Wang, 2005Wang, , 2007Beth, 2006). During reminiscence therapy, at first the participants passively shared their life experiences with others.…”
Section: Changing Of the Depressed Moodsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding was consistent with the results in several previous studies (Ashida, 2000;Haight et al, 2000;Jones, 2003;Wang, 2005Wang, , 2007Beth, 2006). During reminiscence therapy, at first the participants passively shared their life experiences with others.…”
Section: Changing Of the Depressed Moodsupporting
confidence: 94%
“…The evaluation of reminiscence therapy was done using the following tools: Geriatric Depression Scale short form (GDS-SF); Cornell Scale for Depression in Dementia (CSDD), and Hamilton Rating Scale of Depression (HRSD). Results from previous studies have shown that reminiscence therapy improves depressive symptoms, with the average GDS-SF score falling from 13.7-6.36 points to 12.3-4.29 points, and the average CSDD score decreasing from 7.37 to 6.23 points (Ashida, 2000;Jones, 2003;Wang, 2005Wang, , 2007Beth, 2006). The positive effects persisted when measured at 1 and 3 years post-therapy ( p < .05) (Haight et al, 2000).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bu alanlar depresyonu, benlik saygısını, kendini kabullenme, benlik bütünlüğünü, morali, anksiyeteyi, yaşam doyumunu, ziksel aktiviteyi, iyilik halini, bilişsel düzeyi, sağlık durumunu ve yaşam kalitesini içermektedir. [31] Y a p ı l a n ç a l ı ş m a l a r d a a n ı m s a m a n ı n y a ş l ı l a r d a depresyonu [18,19,[32][33][34][35][36][37][38][39][40][41] , yalnızlık duygusunu azalttığı [16,39] ve yaşam doyumunu [42] , benlik saygısını [16,18,43] , psikolojik iyilik halini [39,44,45] , benlik bütünlüğünü [45] , yaşam kalitesini [46] , mutluluğu [20] ve moral düzeyini arttırdığı [37] ortaya konmuştur. Bunun yanında yapılan bazı çalışmalarda anımsama terapisi ile depresyon [16,43,47] , kendini gerçekleştirme [47] , benlik saygısı [20,35] , yaşam doyumu [20,43] ve sağlık algısı [34,35] arasında anlamlı bir ilişki gösterilememiştir.…”
Section: Anımsama Terapisiunclassified
“…[18] Uzun süreli bakım veren kurumlarda sağlık personelinin anımsama grup terapisi için eğitilmesi ve yaşlı grup için böyle bir program sunma gerekliliği belirtilmektedir. [37] Gerontoloji hemşireleri tarafından yapılan anımsama terapilerinin yaşlıların yaşam kalitesini arttırmak için büyük bir potansiyele sahip olduğu ortaya konmuştur. [51] Hemşirelikte anımsama 1960'ların sonuna doğru kullanılmaya başlamış ve 1970'lerde hemşireler deneyimlerini yazmaya başlamışlardır.…”
Section: Hemşirelik Ve Anımsama Terapisiunclassified